Chicken cathelicidin-2 promotes IL-1β secretion via the NLRP3 inflammasome pathway and serine proteases activity in LPS-primed murine neutrophils. (June 2022) - Peng, Lianci; Lu, Yi; Tian, Hongliang; Jia, Kaixiang; Tao, Qi; Li, Gang; Wan, Chao; Ye, Chao; Veldhuizen, Edwin J.A.; Chen, Hongwei; Fang, Rendong
Abstract: Cathelicidins have antimicrobial and immunomodulatory activities. Previous studies have shown that chicken cathelicidin-2 (CATH-2) exerts strong anti-inflammatory activity through LPS neutralization. However, it is still unclear whether other intracellular signaling pathways are involved in CATH-2 immunomodulation. Therefore, the CATH-2-meadiated immune response was investigated in LPS-primed neutrophils. Firstly, inflammatory cytokines release was determined in LPS-primed neutrophils. The results showed that CATH-2 significantly promoted secretion of IL-1β and IL-1α while IL-6 and TNF-α were not affected. IL-1β is the key indicator of inflammasome activation. Next, NLRP3 inflammasome signaling pathway was explored using neutrophils of Nlrp3 −/−, Asc −/− and Casp1 −/− mice and the results showed that the CATH-2-enhanced IL-1β release was completely abrogated, indicating it is NLRP3-dependent. Moreover, CATH-2 significantly induced activation of caspase-1 and gasdermin D (GSDMD) but did not affect LPS-induced mRNA expression of IL-1β and NLRP3, demonstrating that CATH-2 serves as the second signal activating the NLRP3 inflammasome. Furthermore, CATH-2-mediated IL-1β secretion and caspase-1 activation is dependent on potassium efflux but independent of P2X7R. In addition, other signaling pathways including JNK, ERK and SyK were investigated using different inhibitors and the results showed that these signaling pathway inhibitors partially attenuated CATH-2-enhanced IL-1β secretion, especially the JNK inhibitor. Finally, the role of serine protease in CATH-2-mediated NLRP3 inflammasome activation was investigated in neutrophils and the results showed that serine protease activity is involved in CATH-2-enhanced IL-1β secretion and caspase-1 activation. In conclusion, after LPS priming in neutrophils, CATH-2 can be an agonist of the NLRP3 inflammasome. Our study increases the understanding on immunomodulatory effects of chicken cathelicidins and provides new insight on chicken cathelicidins-mediated immune response. Highlights: CATH-2 promotes IL-1β maturation and secretion via the NLRP3 inflammasome pathway in LPS-primed neutrophils. Potassium efflux regulates CATH-2-mediated IL-1β secretion and caspase-1 activation. JNK signaling pathway and serine proteases activity are involved in CATH-2-mediated IL-1β secretion and caspase-1 activation.